Strain-induced mechanotransduction through primary cilia, extracellular ATP, purinergic calcium signaling, and ERK1/2 transactivates CITED2 and downregulates MMP-1 and MMP-13 gene expression in chondrocytes. Issue 5 (May 2016) - He, Z.; Leong, D.J.; Zhuo, Z.; Majeska, R.J.; Cardoso, L.; Spray, D.C.; Goldring, M.B.; Cobelli, N.J.; Sun, H.B.
Summary: Objective: To determine the strain-induced signaling pathways involved in regulating the transactivation of the transcription regulator Cbp/p300 Interacting Transactivator with ED-rich tail 2 (CITED2) and downstream targets in chondrocytes. Methods: Primary human chondrocytes or C28/I2 chondrocytic cells were subjected to various strain regimes. C57BL/6 mice were subjected to treadmill running. Loss-of-function was carried out using siRNA or inhibitors specific for targeted molecules. mRNA levels were assayed by RT-qPCR, and proteins by western blotting, immunofluorescence, and/or immunohistochemical staining. CITED2 promoter activity was assayed in chondrocytes using wild-type or mutant constructs. Results: Cyclic strain at 5%, 1 Hz induced CITED2 expression and suppressed expression of matrix metalloproteinase (MMP)-1 and -13 at the messenger RNA (mRNA) and protein levels in human chondrocytes. Abolishing primary cilia through knockdown of intraflagellar transport protein (IFT88) attenuated CITED2 gene expression and decreased protein levels. Similar effects were observed with inhibitors of extracellular adenosine triphosphate (ATP) or P2 purinergic receptors, or antagonists of Ca 2+ signaling. Knockdown of IFT88 in articular chondrocytes in vivo diminished treadmill induced-CITED2 expression and upregulated MMPs. Knockdown of hypoxia-inducible factor (HIF)1α, specificity protein 1 (Sp1), or deletion of the shear stress response element (SSRE) in the CITED2 promoter limited cyclic strain-induced transactivation of CITED2. However, the strain induced-transactivation of CITED2 was abolished only on knockdown of HIF1α, Sp1, and SSRE or by loss-of-function of IFT88 or extracellular-signal-regulated kinases (ERK)1/2. Conclusions: CITED2 transactivation is a critical event in signaling generated by strain and transduced by primary cilia, extracellular ATP, P2 purinergic receptors, and Ca 2+ signaling. Strain-induced CITED2 transactivation requires HIF1α, Sp1, and an intact SSRE and leads to the downregulation of MMPs such as MMP-1 and MMP-13.